2012
DOI: 10.4085/1062-6050-47.6.13
|View full text |Cite
|
Sign up to set email alerts
|

Five-Day Whole-Body Cryostimulation, Blood Inflammatory Markers, and Performance in High-Ranking Professional Tennis Players

Abstract: Professional tennis players experienced an intensified inflammatory response after the completed tournament season, which may lead to overreaching. Applying whole-body cryostimulation in conjunction with moderate-intensity training was more effective for the recovery process than the training itself. The 5-day exposure to cryostimulation twice a day ameliorated the cytokine profile, resulting in a decrease in tumor necrosis factor α and an increase in interleukin 6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
5
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(137 citation statements)
references
References 28 publications
(40 reference statements)
10
115
5
2
Order By: Relevance
“…[3][4][5]. All intergroup comparisons reveal that mean surface temperature was lower in the group of athletes.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…[3][4][5]. All intergroup comparisons reveal that mean surface temperature was lower in the group of athletes.…”
Section: Resultsmentioning
confidence: 77%
“…Cooling the whole body by extremely low temperatures is regarded as a ''method of recovery'' in biological regeneration. Combining cryostimulation with specialised training enables obtaining a high level of efficiency by an athlete and simultaneously reduces the risk of injuries [5].…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies have shown generally positive results with reductions in the pro-inflammatory cytokines, TNFα (Ziemann et al, 2012;Ziemann et al, 2013), IL-1β , and C-reactive protein and increases in the anti-inflammatory IL-10 (Banfi et al, 2009;Ziemann et al, 2013;Lubkowska et al, 2011), and IL-ra cytokines. However, these studies should be interpreted with caution due to the fact that they were completed under various conditions, not strictly looking at post-exercise recovery.…”
Section: Inflammationmentioning
confidence: 99%
“…However, these studies should be interpreted with caution due to the fact that they were completed under various conditions, not strictly looking at post-exercise recovery. One study was testing WBC on inflammation in obese men (Ziemann et al, 2013), and three others were done over multiple session rather than one session (Ziemann et al, 2012;Ziemann et al, 2013;. Two studies have also noted no changes in TNFα, IL-10, IL-1β, and IL-6 after WBC compared to passive control groups Leppaluoto et al, 2008).…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation